A Design Of Implementation of Information Services in Managing the Emotions of Students in SMA Negeri 1 Koto Salak Dharmasraya - Agustin, Liza (Lembaga Riset Mutiara Akbar, 2022)
This research is motivated by the presence of students who feel irritable, there are students who find it difficult to hold back anger when humiliated or cornered by their friends, there are students who often fight with friends or girlfriends, there are students who cry in class, there are BK teachers who provide information services. but not about managing emotions. The purpose of this study is to describe problems in managing emotions in students, and to design information services in managing students' emotions. This research was conducted using a quantitative descriptive method. The population in this study was 45 participants who were selected by proportional random sampling technique with 43 students. The instrument used is a questionnaire, data analysis using percentage techniques. provide information services using lecture techniques, question and answer, and discussions on the topic of managing emotions. Recommendations to BK teachers to be able to carry out information services about managing these emotions.